Left Ventricle Heart Three Dimension Mechanical Simulation for Kinetic Energy - Mohd Hafizulhadi Mohd Asri; Muhammad Haikal Satria; Arief Marwanto; M. Haider Abu Yazid (IAES Indonesia Section, 2019)
The major drawbacks of current pacemaker are the battery replacement. Patient will need additional surgery to replace the pacemaker unit with the new one. It has been suggested to use rechargeable battery to solve this issue. Recharging a battery within the body, however, is not viable owing to the lifetime of tissue heating and battery charging. For these purposes, the use of piezo-polymer is appropriate as a power harvester for a self-powered pacemaker. Piezo-polymer was commonly used for energy harvesting, but none for implantable cardiothoracic devices. This study focuses on identifying the optimum location on the heart to put the piezo-polymer. This research is conducted by simulation of left ventricle of heart via ANSYS. Heart stress-strain Finite Element Analysis (FEA) are employed to obtain the maximum harvested power. The result shows the location of myocardial contraction that produces sufficient kinetic energy for the placement of the pacemaker. The heart 3-dimensional images are taken from cardiac-CT or cardiac-MRI to search the optimum location on the heart for energy harvesting and minimize pacing energy. Left ventricle electronics model is created to represent the movement of the left ventricle and how piezo-polymer works. In conclusion, the left ventricular wall movement and deformation induced by the movement of the cardiac wall were analyzed in the simulation using the left ventricular model to obtain the place of the peak kinetic energy.